As SIMPL as that: introducing a tax-benefit microsimulation model for Poland - Olivier Bargain; Leszek Morawski; Michał Myck; Mieczysław W. Socha (Institute for the Study of Labor (IZA), 2007)
The Polish tax and benefit system is presented in the context of a recently developed microsimulation model, SIMPL. The model allows simulating direct taxes, social contributions and public benefits in Poland for the years 2003 and 2005. It is based on the Household Budgets Survey data (Badania Budzetów Gospodarstw Domowych) from 2003 and 2005. The document describes details of the Polish tax and benefit system and the simulation assumptions which were necessary in modelling it in SIMPL. We provide information on the quality of the data used in the model and some details of the validation process through various robustness checks. Finally we provide examples of application of the model for analysis of effects of policy reforms.
Keywords: 330; Steuersystem; Sozialtransfer; Mikrosimulation; Einkommensverteilung; Polen